Tax changes in the Czech Republic in the COVID-19 pandemic - Zelenská, Taťána; Bellová, Jana (Review of European and Comparative Law, 2022)
The covid-19 pandemic has since March 2020 led to declarations of several states of emergency, to shutting down of schools, restrictions on gatherings as well as many business activities, with the aim to stopping the spread and transfer of the virus. Apart from the program of compensation bonuses, program Antivirus, postponing of the electronic sales record and so on, the state has reacted to the situation through tax legislation.The presented paper defines some steps as a result of the pandemic that are connected to tax law, these being specifically real estate tax, road tax, value added tax and excise tax.